Effect of Instrumented Hospital Bed on Physical Loads at a Disc Between L5 and S1 Vertebrae During Patient Repositioning - Seyoung Lee; Kitaek Lim; Jongwon Choi; Junwoo Park; Woochol Joseph Choi (Physical Therapy Korea)
Background: Lower back pain/injuries are common in caregivers, and physical stresses at the lower back during patient care are considered a primary cause. An instrumented hospital bed my help reduce the physical loads during patient repositioning. Objects: We estimated the physical stresses at the lower back during patient repositioning to assess biomechanical benefits of the instrumented hospital bed. Methods: Fourteen individuals repositioned a patient lying on an instrumented hospital bed. Trials were acquired for three types of repositioning (boosting superiorly, pulling laterally, and rolling from supine to side-lying). Trials were also acquired with two bed heights (10 and 30 cm below the anterior superior iliac spine), and with and without the bed tilting feature. During trials, kinematics of an upper body and hand pulling forces were recorded to determine the compressive and shear forces using static equilibrium equations. Repeated measures ANOVA was used to test if the peak compressive and shear forces were associated with repositioning type (3 levels), bed height (2 levels), and bed feature (2 levels). Results: The peak compressive force ranged from 836 N to 3,954 N, and was associated with type (F = 14.661, p < 0.0005) and height (F = 10.044, p = 0.007), but not with bed feature (F = 0.003, p = 0.955). The peak shear force ranged from 66 to 473 N, and was associated with type (F = 8.021, p < 0.005), height (F = 6.548, p = 0.024), and bed feature (F = 22.978, p < 0.0005). Conclusion: The peak compressive force at the lower back during patient repositioning, draws one’s attention as it is, in some trials, close to or greater than the National Institute for Occupational Safety and Health safety criterion (3,400 N). Furthermore, the physical stress decreases by adjusting bed height, but not by using tilting feature of an instrumented bed.